Pengaruh Program Aplikasi Sistem Informasi Direktorat Jendral Pajak (SIDJP) Terhadap Kinerja Pegawai Ditinjau dalam Perspektif Ekonomi Islam - Gama Pratama; Nur Muh. Faiz Amin; Yola Fitriyah (Ecopreneur : Journal of Sharia Economics Study Program, 2021)
The influence of the Directorate General of Taxation (Sidjp) information system application program on employee performance is reviewed in the Islamic economic perspective at the Cirebon One Primary Tax Office. This study is motivated by the Financial Institutions Directorate General of Taxes in gaining excellence that guarantees the quality of human resources who are able to provide satisfactory services for tax depositors and prospective tax depositors. aims to determine the effect of the Directorate General of Taxation's information system application program on employee performance reviewed in an Islamic economic perspective (a case study of the Pratama Cirebon One Tax Service Office). This research uses quantitative methods. The results of the research from respondents' answers regarding the sidjp application program (X) obtained an average score of 228.6 and employee performance (Y) obtained an average score of 232.6. Furthermore, based on the results of data analysis using statistical methods, namely simple linear regression. Obtained the coefficient of determination of 02.8% with an R Square value of 0.028. Based on these results it can be concluded that the sidjp application program affects the performance of employees at the Cirebon One Primary Tax Office. Abstrak pengaruh program aplikasi sistem informasi direktorat jendral pajak (sidjp) terhadap kinerja pegawai di tinjau dalam prespektif ekonomi islam di Kantor Pelayanan Pajak Pratama Cirebon Satu. Kajiannya dilatarbelangi oleh Lembaga Keuangan Direktorat Jendral Pajak dalam meraih keunggulan yang menjamin kualitas sumber daya manusia yang mampu memberikan pelayanan yang memuaskan bagi para penyetor pajak dan calon penyetor pajak. bertujuan untuk mengetahui pengaruh program aplikasi sistem informasi direktorat jendral pajak terhadap kinerja pegawai di tinjau dalam prespektif ekonomi islam (studi kasus kantor pelayanan pajak pratama cirebon satu). penelitian ini menggunakan metode kuantitatif. Hasil penelitian dari jawaban responden mengenai program aplikasi sidjp (X) diperoleh rata-rata skor nilai sebesar 228,6 dan kinerja pegawai (Y) diperoleh rata-rata skor nilai sebesar 232,6. Selanjutnya berdasarkan hasil analisis data dengan menggunakan metode statistik yaitu regresi linear sederhana. Diperoleh nilai koefisien determinasi sebesar 02,8% dengan nilai R Square sebesar 0,028. Berdasarkan hasil tersebut dapat disimpulkan bahwa program aplikasi sidjp berpengaruh terhadap kinerja pegawai pada Kantor Pelayanan Pajak Pratama Cirebon Satu.